STRATEGI KEUANGAN UNTUK SISWA SMK: MENYIAPKAN FONDASI KEUANGAN SEJAK DINI - Amelinda, Rita; Tanudjaja, Fahrentz Antonio; Onassis, Gabrielle; Ardiyansah, Rio; Erlina, Annastassia; Wijaya, Kevin (Jurnal AbdiMas Nusa Mandiri, 2026)
Financial planning education is very important including for Vocational High School (SMK) students to prepare for a better future. This topic was chosen due to students’ low awareness of the importance of early financial management, which can lead to financial difficulties in the future. This community service programme aims to increase understanding and practical knowledge of financial planning through interactive and applicable methods, such as seminars, questions and answers, and simple budgeting simulations. The results of the activity showed an increase in students’ understanding of basic financial concepts, such as saving, managing expenses, and planning small investments. In addition, students were able to develop a more structured and realistic personal budget. The programme succeeded in raising awareness of the importance of financial literacy as a foundation for economic independence. These results confirm that financial planning education at the SMK level can be an important step towards building a financially savvy younger generation.